Leading Intergenerational Learning in Organizations: An Example from Turkey - Soner Polöat; Gizem Günçavdı; Yılmazer Yılmaz (European Journal for Research on the Education and Learning of Adults, 2022)
Within the fact that there are members of different generations in organizations nowadays, intergenerational learning in organizations has become more and more important. Some managers are observed to confuse about how to lead intergenerational learning environments in their organizations which makes important to conduct a research on this problem. Thus, this study was conducted and it aimed to understand the intergenerational learning process and how to lead it in a production facility in Turkey. The study group includes 61 people who are employees, team leaders, department directors, field directors and instructors. The study was carried out in the phenomenological research design. The data were gathered through interviews and analysed with content analysis. The results brought out six main themes, which are which are creating zone, acting according to generational differences, increasing motivation, supporting personal development, recording and managing “know-how”, and creating intergenerational respect and understanding.